Integrating Peace Education into Arabic Language Learning at PTKI Aceh - Dhiauddin Dhiauddin (Program Studi Pendidikan Agama Islam, Fakultas Tarbiyah, Institut Agama Islam (IAI) Ibrahimy Genteng Banyuwangi, 2025)
In a region like Aceh, where the echoes of past conflict still shape the present, education carries the weight of healing and rebuilding. This study explores how peace education is thoughtfully woven into Arabic language learning at PTKIN Aceh. Using a qualitative case study approach, data were gathered through classroom observations, conversations with lecturers and students, and a close examination of teaching materials. The findings show that when Arabic is taught through meaningful texts such as verses from the Qur’an, classical poetry, and real-life articles it becomes more than a language lesson. It becomes a space for reflection, dialogue, and the growth of values like empathy, tolerance, and mutual respect. Students shared how learning Arabic in this way helped them see the language as a bridge not just to knowledge, but to one another. Discussions in class sparked deeper awareness, especially when connected to Aceh’s own journey toward peace. Still, the effort is not without its challenges: limited resources, a lack of lecturer preparation in peace-based pedagogy, and students who are just beginning to connect language with life. Even so, the dedication of educators and the richness of the texts used offer real hope. This study suggests that when peace values are intentionally embedded in Arabic instruction, the classroom can become a place where harmony is not only taught but quietly practiced.